Burnout Syndrome in Athletes: Mechanisms, Risk Factors and Prevention - A Narrative Review - Włodarczyk, Franciszek; Zapalska, Magdalena; Kulig, Lidia; Wiercioch, Eliza; Krupska, Barbara Izabela; Włodarczyk, Stanisław; Malec, Julia Anna; Woźniak, Weronika Maria; Wieleba, Marcin; Winiarska, Zuzanna (Quality in Sport, 2026)
Background. Athlete burnout is an increasingly recognized problem in modern sport, associated with high training demands, psychological stress, and environmental pressures. It may significantly affect athletes’ performance, mental health, and long-term engagement in sport. Aim. The objective of this review was to provide an overview of current evidence on athlete burnout, focusing on its underlying mechanisms, key determinants, associated outcomes, and approaches to prevention. Materials and methods. A narrative literature review was conducted using the PubMed and Scopus databases. Publications from January 2016 to March 2026 were included, encompassing original studies, systematic reviews, and meta-analyses addressing burnout in athletes. Results. The reviewed literature demonstrates that athlete burnout develops through complex interactions between physiological strain, psychological processes, and contextual factors within the sporting environment. Major contributors include excessive training demands, insufficient recovery, ineffective coping strategies, and unsupportive coaching conditions. Burnout is linked to declines in athletic performance, deterioration in mental well-being, and increased risk of sport discontinuation. Interventions targeting training regulation, psychological skills, and the social environment appear to play a key role in mitigating burnout symptoms. Conclusions. Athlete burnout represents a complex and multidimensional condition with significant implications for both performance and health. A comprehensive and individualized approach, integrating physical, psychological, and environmental strategies, is essential for effective prevention and management.